2017
DOI: 10.3906/sag-1703-206
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Care Applied Research Network head injuryprediction rules: on the basis of cost and effectiveness

Abstract: Background/aim: Head injuries are commonly seen in the pediatric population. Noncontrast enhanced cranial CT is the method of choice to detect possible traumatic brain injury (TBI). Concerns about ionizing radiation exposure make the evaluation more challenging. The aim of this study was to evaluate the effectiveness of the Pediatric Emergency Care Applied Research Network (PECARN) rules in predicting clinically important TBI and to determine the amount of medical resource waste and unnecessary radiation expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…High level insulin-like growth factor-1 (IGF-1) can enhance the activity of cytochrome P450c17 enzyme, stimulate the follicular membrane to synthesize excessive androgens, and aggravate hyperandrogenemia (Chen et al, 2017, Zhong et al, 2018). Pregnancy rate is related to endometrial receptivity and endometrial thickness, and endometrial dysplasia leads to a reduction in pregnancy rate (Zeng et al, 2018, Azemi et al, 2018, Lungu et al, 2017, Kumar and Kumar, 2017, Gokharman et al, 2017, Gao et al, 2017, Xu et al, 2018). The results showed that total flavonoids of dodder could reduce serum LH/FSH ratio, PRL and INS levels and increase serum P levels, decrease the levels of TNF-α and IGF-1 proteins in ovarian tissue.…”
Section: Discussmentioning
confidence: 99%
“…High level insulin-like growth factor-1 (IGF-1) can enhance the activity of cytochrome P450c17 enzyme, stimulate the follicular membrane to synthesize excessive androgens, and aggravate hyperandrogenemia (Chen et al, 2017, Zhong et al, 2018). Pregnancy rate is related to endometrial receptivity and endometrial thickness, and endometrial dysplasia leads to a reduction in pregnancy rate (Zeng et al, 2018, Azemi et al, 2018, Lungu et al, 2017, Kumar and Kumar, 2017, Gokharman et al, 2017, Gao et al, 2017, Xu et al, 2018). The results showed that total flavonoids of dodder could reduce serum LH/FSH ratio, PRL and INS levels and increase serum P levels, decrease the levels of TNF-α and IGF-1 proteins in ovarian tissue.…”
Section: Discussmentioning
confidence: 99%
“…14 Thus, the conclusion is that North-American physicians, in comparison to Canadian physicians, perform excessive procedures, which results in major increase in hospital expenses. 14 A similar fact was identified in a retrospective study carried out in Turkey, 12 which stated that the improper use of imaging examinations causes major economic losses for hospital UEs. Imaging examinations, when performed without necessity, generate an approximate cost of US$ 20 billion; the non-performance of improper imaging examinations, regardless of the type, could generate an annual saving of US$ 81 billion.…”
Section: Nd Category -The Relation Between Ionization and Possible Mmentioning
confidence: 66%
“…10 It was estimated that 1.5-2% of malignant neoplasms in the USA may have been caused by radiation from CTs. 12 Besides, it is assumed that CTs in the pediatric population may be related to 5,000 future annual cases of cancer. 11 A study carried out in the Netherlands 13 showed that the performance of a head CT increases the risk of developing a future brain tumor.…”
Section: Nd Category -The Relation Between Ionization and Possible Mmentioning
confidence: 99%
See 1 more Smart Citation
“…This qualifies the PECARN rule for grade C1. Four economic analysis studies discussed the positive potential effects of using the PECARN rule on lowering healthcare costs, decreasing the frequency of using CT scans and minimising the exposure of children to harmful ionising radiation [62, 68, 69, 75]. This qualifies the PECARN rule for grade B2.…”
Section: Resultsmentioning
confidence: 99%